Alkyne Versus Ynamide Reactivity: Regioselective Radical Cyclization of Yne‐Ynamides. Issue 8 (18th January 2019) - Dutta, Shubham; Mallick, Rajendra K.; Prasad, Rangu; Gandon, Vincent; Sahoo, Akhila K.
Abstract: Ynamides are typically more reactive than simple alkynes and olefins. However, a serendipitous observation revealed a rare case where the reactivity of simple alkynes exceeds that of ynamides. This led to the development of a unique sulfur‐radical‐triggered cyclization of yne‐tethered ynamides, which involves attack of the alkyne by a thiyl radical followed by cyclization with the ynamide. A wide range of novel 4‐thioaryl pyrroles that could tolerate common functional moieties and N‐protecting groups were expediently constructed by this strategy. The current method contrasts with the typical cyclization of yne‐ynamides, which involves the attack of the alkyne moiety by the ynamide core. Control experiments and DFT calculations supported the participation of the sulfur radical in the reaction and the regioselective cyclization. The synthetic potential of the substituted pyrroles is also discussed. Abstract : Massive attack : An unprecedented radical cyclization of arylthiols with alkyne‐tethered ynamides to give highly‐substituted 4‐arylthiopyrroles is reported. The transformation involves an unusual attack by a thiyl radical on the alkyne motif followed by cyclization with the ynamide core, which shows preferred reactivity of an alkyne over an ynamide. Density functional theory (DFT) studies support the proposed mechanism.